OP0181 Patient perspectives of people with primary sjÖgren's syndrome: a multicentre qualitative european study. (12th June 2018) - Unger, J.; Mattsson, M.; Dragoi, R.; Boström, C.; Buttgereit, F.; Lackner, A.; Witte, T.; Raffeiner, B.; Peichl, P.; Hermann, J.; Dejaco, C.; Stamm, T.
Abstract : Background: Primary Sjögren's syndrome (pSS) is one of the most common systemic autoimmune disorders and leads to an impaired health related quality of life. However, treatment mainly focuses on the management of physical manifestations. Little is known about the lived experiences of people with pSS, including the impact on people's life, functioning and their social relationships. Objectives: To explore the perspectives of people with pSS from different European countries with various cultural backgrounds in order to achieve a broad understanding of concepts that are important and meaningful to people with pSS. This study is a part of a project which aims to evaluate the coverage of the patient perspectives by patient reported outcome measures in pSS, which is funded by the Austrian Association of Rheumatology. Methods: A multicentre focus group study was performed in five European countries, namely Austria, Germany, Italy, Romania and Sweden. Patients were recruited from the outpatient clinics of the local centres. Focus groups were chaired by a trained moderator and followed an interview guide which included questions about impairments and limitations in body structures, body functions, activities and participation as well as contextual factors and resources, such as coping strategies. Focus groups were audiotaped and transcribed. We conducted a content-analysis of each focus group and subsequently combined the extracted concepts from each country, using the International Classification of Functioning, Disability and Health as a frame of reference. Results: A total of 12 focus groups was conducted in seven participating centres in five countries. Fifty people (48 women; 96%) with pSS participated in the focus groups (ranging from two to four groups per country). All focus groups had a total duration of 1030 min and resulted in 252 pages of transcript. From qualitative analysis we derived concepts meaningful to people with pSS from all countries, especially those concepts that were linked to a physical dimension. However, we identified differences in the description of these experiences in daily life, for example for pain-concerning sensations or for the impact on social relationships. Furthermore, the attitudes towards the treatment and towards the disease differed between the participants. People with pSS had various coping strategies, such as gaining more knowledge about the disease or utilising non-pharmacological treatment. Conclusions: This is the first multicentre qualitative European study which investigated the patient perspectives in pSS with a cross-cultural understanding. Clinicans, health professionals and researchers need to know about the perspectives, experiences and needs of people with pSS in order to ensure a comprehensive treatment. Disclosure of Interest: None declared